Drug residues in syringes and other injecting paraphernalia in Hungary. Issue 2 (18th July 2017) - Péterfi, Anna; Csorba, József; Figeczki, Tamás; Kiss, József; Medgyesi‐Frank, Katalin; Posta, János; Gyarmathy, V. Anna
Abstract : The appearance and spread of new psychoactive substances (NPS) is a phenomenon seen throughout Europe since 2008. Synthetic cathinones, a group of NPS, have been self‐reported as the drug injected by the vast majority of people who inject drugs (PWID) in Hungary. This study aims at updating our knowledge of what exactly are the compounds injected by PWID. This multi‐site study analysed residues from used injecting drug paraphernalia collected from PWID via low‐threshold services and from public places in Budapest, Debrecen, Miskolc, Szeged, Békéscsaba and Pécs between March 2015 and February 2016. The paper describes the results of the chemical analysis of 2985 analytical samples created out of the 22 005 objects collected in this period. Active agents and their occurrences (compound cases) were identified using GC–MS. The study detected 161 different compounds, mostly synthetic cathinones (29%), non‐psychoactive compounds (14%), amines (12%), non‐psychoactive medications (12%) and other substances (32%). Of the 12 762 compound cases, 50% were cathinones, 18% substitution medications, 9% non‐controlled psychoactive substances and 24% other substances. Among compound cases, the most frequent cathinones were pentedrone (21%) and α‐PHP (12%). Among substitution medications, most were methadone (93%), and non‐controlled psychoactive substances were caffeine (74%) and nicotine (21%). Overall, the most prevalent substances were methadone (16%), pentedrone (10%) and caffeine (7%) with considerable variation detected among participating cities. Our results are consistent with previous self‐reported data showing a high prevalence of synthetic cathinone injection among PWID in Hungary. We also detected a large‐scale misuse of methadone by PWID. Abstract : The injection of synthetic cathinones as the main pattern among Hungarian people who inject drugs and the large‐scale diversion and abuse of methadone are the main results of the study. The findings are based on the chemical analysis of used and discarded injecting paraphernalia collected throughout a 12‐month period involving seven study locations in Hungary.